(untitled) (Journal of Partial Differential Equations, 2017)
" In this article, the space-time fractional Benjamin-Bona-Mahoney equation is investigated via applying the first kind of elliptic equation method. As a result, based on the B00e4cklund transformations and some seed solutions of the first kind of elliptic equation, families of infinite sequence solutions are presented. This approach is also applicable to many other nonlinear fractional differential equations."